Effect of local restaurant smoking regulations on progression to established smoking among youths - Michael Siegel; Alison B. Albers; Debbie M. Cheng; Lois Biener; Nancy A. Rigotti (2005)
Background: While smoke-free restaurant laws are intended to protect the public from secondhand smoke exposure, they may also discourage smoking among adolescents. There is no evidence from longitudinal studies to test this hypothesis. Objective: To examine the effect of local restaurant smoking regulations on progression to established smoking among adolescents. Design, setting, and subjects: A cohort of 2623 Massachusetts youths, ages 12–17 years at baseline, was interviewed via random digit dial telephone survey in 2001–2002 and followed up two years later. A generalised estimating equations (GEE) logistic regression analysis was used and controlled for potential individual, household, and town level confounding factors. Main outcome measure: Progression to established smoking during the two year follow up period (defined as having smoked 100 or more cigarettes in one’s life). Results: Compared to youths living in towns with weak regulations, those living in towns with strong regulations (complete restaurant smoking bans) had less than half the odds of progression to established smoking (odds ratio (OR) 0.39, 95% confidence interval (CI) 0.24 to 0.66). The association was stronger for youths in towns with strong regulations in effect for two or more years (OR 0.11, 95% CI 0.03 to 0.37), although it was still present for those in towns with strong regulations in effect for less than two years (OR 0.55, 95% CI 0.33 to 0.90). No relationship was found between living in a town with a medium restaurant smoking regulation (restriction of smoking to enclosed, separately ventilated areas) and rates of progression to established smoking. Conclusions: Local restaurant smoking bans may be an effective intervention to prevent youth smoking.